Multievent Correlation with Neutron Volume Detectors - Noah Nachtigall; Andreas Houben; Richard Dronskowski (Quantum Beam Science)
The development of advanced volume detectors for neutron time-of-flight diffractometers offers exciting new possibilities. This work takes advantage of these advances by implementing a novel data preprocessing algorithm, exemplified for the first time with data acquired during the operation of a singular mounting unit of the POWTEX detector placed at the POWGEN instrument (SNS, ORNL, Oak Ridge, TN, USA). Our approach exploits the additional depth information provided by the volume detector needed to correlate multiple neutron events to neutron trajectories of similar origin and probability. By comparing the properties of these trajectories with the expected physical behavior, one may first identify, then label, and ultimately remove unwanted events due to phenomena such as secondary scattering within the sample environment. This capability has the potential to significantly improve the quality and information content of data collected with neutron diffractometers.